The Collaboration in Socializing Policies of Covid-19 Pandemic - Evi Satispi; Lusi Andriyani; Djoni Gunanto; Devia Andiani (Program Pascasarjana Universitas Negeri Makassar, 2021)
Role of regional government in socializing the policy produced by SKPD of this local government is an obligation for every apparatus to socialize that policy so that the society, as the main receiver of the related polciy, will get their rights and obligations properly. The communication of regional government in this research can be discussed in more explicit regarding the flow of that communication delivery from the government to the community. The method used in this research was decriptive with qualitative approach and applied the theory of Edward III to see the stages of communication in its role in socializing the policy of the Government of South Tangerang City. Those types of socialization media were main instruments of regional government pf South Tangerang to socialize policies. There was another type of socialization namely direct media or socializing to every neighbourhood. The conclusion of this research was that the socializing of policies has been conducting through various types of media; online, printed, and electronics. The Office of Communication and Informatics of South Tangerang City played its role also in regards to socialization by cooperating with Press Councils to monitor the behaviors of media. It is suggested that th e Government of South Tangerang City keeps improving their performance in socializing policies so that these will reach the purposes of the policies produced in order to build law order society towards the policies made.